The Challenges of Adoption of Eco Single Currency among ECOWAS Member-States - Anele, Livinus; Anuga, Joseph (African Journal of Politics and Administrative Studies, 2024)
The Economic Community of West African States, ECOWAS, had an agreement to adopt the Eco as its single currency for the fifteen member-states of the West African Sub-regional organization. This major objective has failed to materialize after a long period of time. This paper, therefore seeks to highlight the major challenges confronting the Eco currency project. Data were collected from secondary sources, using content analysis. The paper of discusses the challenges facing the proposed Eco single currency in West Africa, discusses the theoretical framework of monetary integration using Mundell’s factors of Mobility Theory and Mundell’s Optimum Currency Area Theory applied. Based on the findings, Some of the challenges facing the proposed Eco currency in ECOWAS include lack of political will, influence of France on its former territories in West Africa, membership of multiple regional blocs by member states of ECOWAS and fear of domination of the smaller states in the bigger ones. Other challenges include; security and political challenges, inadequate legal instruments to enforce treaty obligations, inadequate modern infrastructure among others. To make this proposed Eco currency a success, the paper suggests that West Africa Monetary Zone member states must take concrete action by showing political will towards the creation of Eco currency area in West Africa. There should be clearly spelt out benefits and costs accruing to each member state in the proposed Eco community currency area. All member states of ECOWAS must be treated as equal partners.
Keywords: Adoption; Anglophone-Francophone; Development; ECOWAS; Eco single currency

From red tape to red carpet: the Unidroit Cape Town Convention and MAC Protocol’s Adventure in Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2024)
This article examines the implementation of the Mining, Agricultural and Construction (MAC) Equipment Protocol under the Cape Town Convention in Africa, focusing on enhancing economic growth and sustainable development through improved access to financing for high-value mobile equipment. Africa’s economic development is significantly hindered by inadequate infrastructure, which escalates transaction costs and limits access to international markets. Investment in modern infrastructure, particularly in the mining, agricultural, and construction sectors, is typically expensive for many businesses in the African region. The MAC Protocol aims to address these challenges by providing a uniform legal framework that supports the financing of MAC equipment. The Convention and the MAC Protocol facilitate access to affordable capital and reduce risks for financiers who take international interests in MAC equipment, promoting economic activities in Africa. The article highlights the legal protections offered by the MAC Protocol, ensuring rights against third-party claims and enhancing the enforceability of international interests. The adoption of the MAC Protocol by African States could significantly impact their ability to meet the United Nations Sustainable Development Goals by making modern, cost-efficient equipment more accessible, thus boosting productivity and economic diversification. The article advocates for adopting the MAC Protocol, emphasizing its potential to enhance foreign investment in the mining, agriculture, and construction sectors, stimulating economic development in Africa. This strategic move will propel African countries towards greater economic resilience and integration into the global economy. The article also critically analyses and illustrates the several declaration mechanisms available to countries adopting the MAC Protocol, accompanied by a guidance note to sensitize lawmakers when signing and/or ratifying or acceding to the Cape Town Convention and the MAC Protocol.

The efficient enforcement challenge of secured transactions law reforms in civil law systems: self-help repossession, strict foreclosure, and other methods for the acceleration of enforcement of security interests - Tajti (Thaythy), Tibor (Uniform Law Review, 2024)
Although the forging of an efficient system for enforcement of security interest is one of the central expectations of secured transaction law reforms in civil law systems, the results hardly give reason for satisfaction. As the reforms tend to be supported and influenced by various international organizations’ projects (especially the World Bank, the European Bank for Reconstruction and Development, the International Institute for the Unification of Private Law, and the United Nations Commission on International Trade Law), most out-of-court methods of enforcement of security interests have played a central role. Yet due to civil law’s general hostility towards self-help as such, either the introduction of the concept has been rejected or the local limited-reach kin have been merely ‘paper tigers’. Similarly, although security interests on several types of collateral (accounts, investment property) or on the workhorse of the English financial system—the floating charge—have also been enforced extrajudicially (save the exceptions), little attention has been attributed to these enforcement modalities. The same applies to strict foreclosure in civil law systems still being prohibited, or restricted, and thus rarely resorted to, due to the inherited hostility towards the doctrine of lex commissoria. Rethinking local laws on preliminary and temporary court orders to match them with such globally known ex parte preliminary measures as the English Mareva Injunction or the French Saisie Conservatoire, which allow creditors to swiftly freeze debtors’ assets and thus substitute self-help repossession, has also been given short shrift. The enforcement segment, consequently, remains the Achilles’ heel of secured transaction law reforms in civil law systems. This article desires to contribute to reform literature by addressing these deficiencies and by offering tested, fully or partially fitting, functional equivalents of self-help repossession.

States and Regional International Organizations - Zouapet, Apollin Koagne (International Organizations Law Review, 2024)
Beyond the thorny, even insoluble question of the definition of a region and the definition of the criteria that should make it possible to apprehend the polymorphism of rio s, the raison d’être of these organizations, their mode of operation and their activities are at the heart of the debate on “international governance”. For many authors, the advent of RIO s has often been seen as a challenge to the state monopoly in the international legal order and a redefinition of the relationship between these particular organizations and states. It is this relational dynamic between the States and the RIO s that this contribution aims to describe and analyse. The aim is to examine the originality and specificity of the relationship between the RIO s and the States, compared to the latter’s relationship with the ‘classic/universal’ ios, which would reveal something about the very nature of regional organizations.
PDF: https://brill.com/downloadpdf/view/journals/iolr/21/1/article-p147_008.pdf
Keywords: Cooperation; Instrumentalism; Integration; Regionalism; Supranationalism; Universalism

The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On - Heyns, Christof; Viljoen, Frans Jacobus; Murray, Rachel (Brill, 2024)
This collection of chapters tracks and explains the impact of the nine core United Nations human rights treaties in 20 selected countries, four from each of the five UN regions. Researchers based in each of these countries were responsible for the chapters, in which they assess the influence of the treaties and treaty body recommendations on legislation, policies, court decisions and practices. By covering the 20 years between July 1999 and June 2019, this book updates a study done 20 years ago.
PDF: https://brill.com/downloadpdf/edcollbook-oa/title/38945.pdf
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives

The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal - Kane, Ibrahima (The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On, 2024)
"Chapter 16 The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal" published on 09 Feb 2024 by Brill | Nijhoff.
Section: The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives; Social Sciences

Uniform Law: Legal Responses to Globalisation - Basedow, Jürgen; Max-Planck-Institut für Ausländisches und Internationales Privatrecht (Hamburg, Germany) (Mohr Siebeck, 2024)
International conference proceedings
Keywords: COMMERCIAL LAW; Economic Analysis; PRIVATE INTERNATIONAL LAW; Uniform law

Measuring the Effects of Post-Convention Activities at the HCCH - Zhang, Ke (McGill University, 2024)
https://escholarship.mcgill.ca/concern/theses/cn69m944k
Keywords: HCCH; Hague Conference on Private International Law

Nigeria’s Contribution to Africa’s Regional Integration: Assessment of its recent Performance - Garba, Dimas (African Journal of Politics and Administrative Studies, 2023)
This paper investigates the recent performance of Nigeria towards Africa’s regional integration as a major power in Africa. The main objective of the research is to determine the extent of Nigeria’s commitment to the realization of the African Union’s vision of becoming a fully integrated, prosperous and peaceful Africa; and a dynamic force at the global level. Since her independence in 1960, Nigeria has been widely acknowledged as a leading power in Africa (The Giant of Africa) by several studies because of its preponderant political, economic and militarily power; influence; and benevolent contributions regarding to the liberation and progress of Africa. However, there are hardly substantive assessments of its recent performance towards Africa’s integration. The study adopts the Hegemonic Stability Theory; and descriptive analysis method to analyze data obtained from secondary sources. Analysis of the 2016 and 2019 Regional Integration Index (ARII) reports covering the period from 2010-2019 reveals that Nigeria has performed poorly towards the continent’s integration among its peers, both at the continental and sub-regional levels. The paper concludes that Nigeria’s poor performance would significantly slow the acceleration of Africa’s integration; and the country risks losing its leadership position in Africa to its rivals, especially South Africa. It recommends that the Nigerian government should take deliberate steps in formulating and implementing policies that would improve its performance across the five dimensions of the regional integration; and it should strengthen its commitment to consolidate its leadership position in Africa, and motivate smaller countries to contribute their best.

The Challenges of Regional Integration and Effective Implementation of African Continental Free Trade Area (AfCFTA) Policy in Africa - Garba, Dimas; Wancelous, Avong (African Journal of Politics and Administrative Studies, 2023)
The paper is an investigation of the challenges of regional integration in Africa and their effects on the implementation of the African Continental Free Trade Area (AfCFTA) policy. The major objective of the paper is to proffer solutions to the challenges for the effective actualization of the policy. The assumptions of the neo-liberal theory were used to support the AfCFTA initiative to promote economic growth and development in Africa. The data used to advance the argument were obtained from secondary sources of data collection. The study finds that language barrier, multiple currencies, porosity of borders, foreign interference, political instability and insecurity, poor human development, over-lapping of membership of sub-regional organizations, poor state of infrastructure, and state-centric nature of integration initiatives are some of the core challenges hindering the effective execution of the AfCFTA policy. The study recommends that the African Union (AU) should intensify effort at realizing a single currency policy for Africa; design comprehensive regional security architecture to include high technological surveillance, joint air and ground border patrol among member states of Regional Economic Communities (RECs) to address trans-border crimes and insecurity. There should also be institutionalization of counterpart funding among AU member-states for infrastructural development; and encouragement of private and civil society participation in the integration initiative, among others. In concludes that if the challenges identified are not effectively addressed, it will be very difficult for the AU to successfully realize the objectives of the AfCFTA policy.
Keywords: AfCFTA Policy; Africa; Challenges; Implementation; Regional integration

The application of knowledge stylised facts in West Africa Economic and Monetary Union (WAEMU) - Amanzou, Nogbou Andetchi Aubin; Ballo, Zie; Troupa, Sery Guy Flavien (Journal of Innovation and Entrepreneurship, 2022)
Sub-Saharan Africa has one of the dynamic economies in the world. Unfortunately, the performance achieve has not led to a reduction of social issues. So, the government are making massive investment to overcome social issues. This massive public investment highlights the exogenous nature of the current economic growth. So, a change of the strategy in the economic management of sub-Saharan Africa is required. One solution remains the change of economic paradigm: the transition from exogenous economic with decreased return to endogenous economic with increased return. The theoretical explanation of such arguments are supported by New Growth Theory. However, the implementation of the new theory required compliance to a set of indicators known as stylized facts. In 2009, Romer and Jones have developed a list of stylized corresponding to the need of New Growth Theory. The stylized facts of the West African Economic and Monetary Union (WAEMU) have been compared to the standard facts of Romer and Jones in order to apply the recommendations of New Growth Theory in this area. To reach that aim, the stylized facts have been described and analysed with econometric panel model. As result, we find that the description of the stylized facts in WAEMU fitted perfectly with that of Romer and Jones for the same period. Unfortunately, when using data, institution don’t work as expected by Romer and Jones. This study strengthens the argument for the implementation of economic policy based on the valorisation of knowledge economic in WAEMU.
Keywords: Africa; D83; Economic development; Economic growth; Knowledge economic; Macroeconomic Analyses; N17; O11; O17; O40

Relationship between International and Domestic Law in the Constitutions of the States of the Economic and Monetary Community of Central Africa - Mairema, Jacqueline (Journal of Law and Criminal Justice, 2022)
The purpose of this paper is to analyze the constitutional provisions relating to the relationship between international law and domestic law of the States of the Economic and Monetary Community of Central Africa reveals an ambivalent conception of the system relationships. This is all the more true since the choice of monism with primacy of international law is affirmed both formally and materially. Even if this variant of monism seems to be tempered by certain constitutional provisions, the treaties have considerable effects in the domestic legal order. Once integrated into the legal order through the modalities of insertion, treaties have a supra-legislative and infra-constitutional rank. However, some constitutions of the States of the Economic and Monetary Community of Central Africa, such as Gabon and Equatorial Guinea, have not enshrined constitutional provisions on the place of treaties in the legal order. The concern to safeguard the supremacy of the constitution and consequently of national sovereignty may justify such a constitutional practice.
Keywords: Droit d’origine externe; Dualism; Insertion; International law; Monism; Monisme; National law; System relationship; Sécurité juridique

Rising from its ruins? The Southern African Development Community (SADC) Tribunal - Shumba, Tapiwa (Law, Democracy and Development, 2022)
The Tribunal of the Southern African Development Community (SADC) was established to ensure adherence to and the proper interpretation of the provisions of the SADC Treaty and its subsidiary instruments, and to adjudicate upon such disputes as might be referred to it. However, since its establishment, it has had a troubled history. After the rulings it made against the Government of Zimbabwe in the landmark Campbell land seizures case, the Tribunal's operations were unceremoniously suspended. This was followed by a process to revise its mandate, one that ultimately condemned it to paralysis and ruin. The new 2014 Protocol on the Tribunal, meant to revise the mandate of the Tribunal to confine it to hearing disputes involving states only, has been criticised as an attempt to undermine the rule of law and human rights in the region. Since the adoption of this 2014 Protocol by the SADC Summit, stakeholders have mobilised regionally to resist its ratification by member states. In particular, lawyers in SADC countries are embarking on legal petitions to reverse the Protocol and promote the revival of the Tribunal in terms of its old mandate. So far, there have been victories in these cases in two influential SADC member states, South Africa and Tanzania. However, it remains important to assess the significance of these developments. As such, the article raises the question: Is the Tribunal rising from its ruins?
Keywords: Regional integration; Rule of law; SADC Tribunal

Emergence in the WAEMU and EMCCA areas - Ntwali, Valéry IRAGI; Centwali, Guillain CIRHUZA (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The Economic and Monetary Community of Central Africa (EMCCA) and the West African Economic and Monetary Union (WAEMU) have succeeded in stabilizing their monetary systems, but this monetary stability has not been accompanied by real emergence. The economies of most of the member states of these two organizations are based on commodities and cocoa, which means that they are completely volatile and therefore lack the stability necessary for real emergence. This study based mainly on documentary research through the exploitation of reports produced by various international and regional institutions such as the IMF, the World Bank, the African Development Bank, ECOWAS, etc., and the writings of various emergence theorists, shows the role that industrialization and diversification of the economies of the WAEMU and EMCCA zones should play in the development of the economies of the member states and the improvement of the living conditions of the populations.
Keywords: CEMAC; Emergence; Spaces; UEMOA; WAEMU

The impact of multilateral trade agreements on intra-regional trade : the case of SADC and ECOWAS - Osarumwense, Uwakata Yvonne (University of South Africa, 2021)
This study examines the comparative impact of multilateral trade agreements on intra-regional trade in the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) regions in Africa. Annual data was gathered from 2000 to 2018 and dynamic panel data and econometric techniques were used to control for individual country characteristics, endogeneity, serial correlation, heteroscedasticity and interdependencies between the countries in each region. Two estimations were done, one using the tariff measures of multilateral agreements, the second using non-tariff measures of multilateral agreement. The results of the empirical analysis show that the SADC region has a slight edge over ECOWAS in terms of technological progress and investment, especially in trade infrastructure. However, the ECOWAS levels of employment and economic growth are higher than those in the SADC region. These differences further translate into differences that drive intra-African trade in these regions, and how they relate to the role of multilateral agreements in intra-African trade in each of these regions. While technology and investment are key drivers and enhancers of intra-African trade in SADC countries, economic growth and employment stand out as key enhancers of intra-African trade in ECOWAS, especially where multilateral agreement is represented by tariff measures. This study reports that when non-tariff measures are used to represent multilateral agreements, export trade costs, in addition to investment and technology, are the key drivers of intra-African trade in SADC countries. For ECOWAS, under non-tariff measures of multilateral agreements, only economic growth drives intra-African trade.
Keywords: Commercial treaties; Customs unions; Institutional environment; Intra-African trade; Investments; Multilateral agreement; Panel data estimation; Tariff and non-tariff trade barriers

Harmonization (or rather Standardization) of Cooperative Law in the OHADA Zone: What is the Result after Ten Years of Implementation of the Uniform Act? - Tadjudje, Willy (CIRIEC - España. Revista jurídica de economía social y cooperativa, 2021)
The Uniform Act related cooperative societies (UA-COOP) is the main source of cooperative law in all the seventeen States parties to the OHADA founding Treaty. Ten years after its entry into force (2011-2021), the aim of this study is to assess the level of enforcement of this Act. More concretely, the aim is to compare the state of cooperative law at the time of the entry into force of the UA-COOP (2011) with the current situation (in 2021). Such a comparison should make it possible to assess the contribution of the UA-COOP to the development of cooperative law and strengthening of national cooperative movements in the OHADA zone.

Economic Community of West African States at forty-five: a fool at forty-five a fool forever? - Nwosumba, Victor (African Journal of Politics and Administrative Studies, 2020)
Amid COVID-19 pandemic lockdown in the year 2020, Economic Community of West African States hereafter called ECOWAS quietly celebrated its forty-five years of establishment. Widely, much was not heard of or written about the community probably due to the challenges of the pandemic. However, the address of the President of ECOWAS Commission to the staff of ECOWAS institutions on the occasion of the commemoration of the community’s forty-fifth anniversary serves as a reminder that attention should also be given to this regional giant against all odds. Thus, the purpose of this paper is to celebrate ECOWAS at forty-five and then examine whether it is a fool at forty that is proverbially referred to as a fool forever. The paper, through thorough examination of the data collected from secondary sources finds that ECOWAS is still far from achieving its main mandate, its achievements as orchestrated by His Excellency, the President notwithstanding. The paper argues that the postponement of the establishment of ECO, a common currency for the region for the sixth time from 2020 to yet to be announced date, lack of realistic free movement of persons and goods among members and selfish interests of its leaders in the guise of national interest are enough reasons to conceive ECOWAS as a fool at forty-five. With the aid of constructivist theory,it concludes that even if ECOWAS at forty-five is still fooling around it has the chances of not being a fool forever if the leaders should turn a new leaf and pursue the attainment of the community’s mandate before its fiftieth anniversary.

The Effectiveness of the Harmonization Tool Adopted Under the Ohada Regime - Ceesay, Buba (Social Science Research Network, 2020)
The Organization for the Harmonization of Business Law in Africa, OHADA, is a regional entity whose primary objective is to harmonize the Business Law of its members. It has adopted legislative measures and institutional setups to ensure the realization of this object. This paper critically examined the effectiveness of the harmonization tool adopted under OHADA. The paper first gives a brief overview of OHADA setups, then the advantages and shortcomings of the harmonization tool adopted under the OHADA regime and finally concluded that though OHADA is a major step towards the attainment of harmonization of business law and Integration with the view of fostering development and business activities, its harmonization tool is lacking full efficacy towards the attainment of the objectives of the organization due to prevailing limitations and challenges.
Keywords: SSRN

The OHADA Structure as a Possible Model for the Development of a Commercial Law Structure in the Southern African Development Community (SADC) - Leno, Ngaundje Doris (International Journal of Social Sciences and Management Review, 2020)
The Southern African Development Community's (SADC) colonial legacy which introduced foreign legal traditions and the consequences of the diversity heighten the urgency for unified commercial legislation to deal with cross-border disputes.Thus, the issue is whether the Organisation for the Harmonisation of Business Law in Africa (OHADA) structure can serve as a possible model for the development of a uniform commercial law structure in the SADC .Despite the success of the OHADA, the author submits that the OHADA can only serve as a source of inspiration, or roadmap, providing guidance to the SADC drafters.The paper aims at demonstrating that the OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC.The significance of this paper lies in the contributions it makes to the development of a commercial law structure in the SADC.
OpenAlex: https://openalex.org/W3124748692
Keywords: Development; Integration; Model; OHADA; SADC

Algeria and the African Union - between security and economic integration: a neofunctionalist and regionalist reading - Lamri, Amel (Canterbuy Christ Church University, 2020)
This thesis investigates the process of integration in the African Union (AU), and the reasons behind the slow progress of the AU to achieve the goal of deeper economic integration. In the research I explore the role of an AU member state in the process of African integration: Algeria. The research scrutinises the development of Algerian foreign policy towards the AU and highlights any changes in the Algerian FP attitudes and the reasons behind these changes. Similarly, the research unveils the reality of the decision-making process in this country, and the different agents that influence it. To achieve the main goals of the research, different theoretical choices were elaborated. This resulted in researching European integration theories; Neofunctionalism was, then, selected to study the Algerian development in the making of its foreign policy in general and towards the African Union specifically. Some concepts within the Neofunctionalist thinking were used including the principle of the shift of loyalties, the socialisation process, the spillover system, and the role of interest groups in the process of integration. Moreover, the theory of Regionalism was used to examine the process of integration in the AU discovering new reasons that led to the slow development of economic integration in Africa. Consequently, the research highlights the current obstacles and challenges that have hindered the process of economic integration in the AU, including the poverty of most of the AU member states, the limited financial budget of the Union and the instability of the majority of African countries. Furthermore, the research unveiled the lack of political will towards AU economic integration plans. Hence, this contribution extends beyond the traditional models of explanation, and discusses the situation in AU member states (in this case Algeria) and points to other factors as well such as the weakness of the lobbyist activities and business groups in Algeria specifically and Africa more generally. The thesis, then, focusses on Algeria’s supportive and active status in the AU security sector, highlighting how Algeria has been successful in pushing its own security and antiterrorism agenda to the AU level, thereby demonstrating that integration into the AU is possible, if it is backed by influential member states, and wider coalitions can be built to promote integration and cooperation.
Permalink: https://repository.canterbury.ac.uk/item/8y60y/algeria-and-the-african-union-between-security-and-economic-integration-a-neofunctionalist-and-regionalist-reading
Keywords: Africa Union; Algeria; Intégration régionale

The role of the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) in facilitating continental integration - Luthuli, Isaac (University of KwaZulu-Natal, 2020)
The dissertation examines the role the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) can play in facilitating the political and economic convergence of the African Union (AU) member states. The developmental challenges facing Africa in spite of its wealth of human and natural resources is poignant. The genesis of this problem can be traced to the history of colonialism and the wave of independence in the continent in the late 1950s. Arguments have been put forward to suggest that one of the most viable ways of promoting Africa’s development is by developing and promoting intra-continental trade which can be possible through continental integration. The specific areas reviewed are regional stability and how intra-regional trade and investment is used to promote economic convergence. Africa's need for political and economic integration at a continental level is further sustained by the assumption that neocolonialism can be blamed for the weakness of structures in African states. Some scholars agree on the idea that regionalisation is often seen to offer a possibility to respond to the challenges of globalization. This impact nevertheless is dependent on the relation between globalisation and regional sentiment. Regional integration implies a form of interdependence among nation-states. Such interdependence leads to an establishment of regional integration arrangements between sovereign states within a geographical space. These agreements are shaped formally and there is a commitment to work together in order to realise political and socio-economic benefits. This study maintains that in order to achieve effective integration of the continent, Nigeria and South Africa as case studies, as continental giants have a key role to play to this end and as members of ECOWAS and SADC respectively. It is argued here that both the SADC and ECOWAS as sub-continental blocks have made some notable and commendable progress in developing policies for trade liberalization and economic integration, this, however, is not enough as such policies are also pertinent at a continental level. The study found that SADC and ECOWAS as regional blocks can play a role in aiding the continent to achieve a trade liberalization to achieve continental economic development.
https://researchspace.ukzn.ac.za/handle/10413/18708
Keywords: African integration; ECOWAS; Economic Development; Economic convergence; Integration; Intra-continental trade; SADC

A Comparative Study of ECOWAS and ECCAS towards Implementation of the Abuja Treaty - Nyasembi, Kevin Selassie (University Of Ghana, 2019)
The Abuja Treaty is the blueprint and reference point for continental-level economic integration that was first established in 1991 to see to the creation of an African Economic Community (AEC). The Treaty acknowledges that, the African continent, as a unified unit of countries, wields immense power in the international system, in terms of trade and political influence, and thus it seeks to bring to fruition a highly integrated Africa. This study strives to evaluate the progress made on the implementation of the Treaty Establishing the African Economic Community (AEC) by comparing two regional blocs, the Economic Community of Central African States (ECCAS) and the Economic Community of West African States (ECOWAS), which serve as 2 of 8 building blocks for the realisation of the AEC. Accordingly, the research method used was qualitative and employed a purposive sampling method that draws on the selection of experts in the field of regional integration to shape the outcome of the study. The research findings include the fact that regional integration, on the continent, has progressed positively although it manifests slowly. Additionally, it found that both the ECOWAS and the ECCAS have progressed in terms of the implementation of the stages of the Abuja Treaty, although the former surpasses the latter in this regard. Yet, in spite of their progress, both RECs have faced challenges unique to their regions. ECOWAS for instance faces the problem of inability to completely enforce protocols on free movement of persons. The lack of national implementation of free movement legislation creates avenues for its ineffectiveness. Border checks are commonplace and there is very little standardization of official forms. ECCAS on the other hand faces a problem of overlapping goals and ideas with CEMAC as well as the failure of member states to carry out agreed decisions within their states due to issues such as conflict and instability in the region. On a whole, the study refutes the common idea that the Abuja Treaty has not been implemented at all but only sees its implementation as slow-paced.

Unification of international sales law in the SADC region : the role and significance of the CISG - Simelane, Mbalenhle Pearl (University of Johannesburg, 2019)
The United Nations Commission on International Trade Law (UNCITRAL) is one of the most prominent legal bodies in international commerce. In 1980, the final draft of the United Nations Convention on Contracts for the International Sale of Goods (CISG or the Convention) was approved by the United Nations (UN) General Assembly and came into operation on 1 January 1988. Generally, the diversity of laws is an impediment to international and regional trade. Traders are discouraged from entering into international sales contracts due to the dissimilarities of legal systems. However, the CISG seeks to unify laws relating to the international sale of goods, whilst codifying the existing rules of international trade. The main objectives of the Southern African Development Community (SADC) are to achieve development and economic growth through regional integration.1 The legal integration and unification of sales law has a significant role to play in regional integration. Hence, SADC would do away with difficulties that affect interregional and intra-regional trade by impeding economic growth by making use of widely accepted trade laws, such as the Convention. International trade promotes both economic development and social upliftment. Moreover, democracy, political stability and human rights must be respected to foster sustainable economic growth and development in Southern Africa. 2 With advantages such as accessibility, flexibility, indorsing party autonomy, simplicity, and uniform interpretation, the paper revisits the call for the unification of laws on the sale of goods in SADC and considers the role and significance of the CISG in the region. LL.M. (Commercial Law)
Keywords: Commercial law; International economic integration; International trade Law; International unification

The role of the SADC Protocol on Trade in Services in regional integration - Swanepoel, L. B. (North-West University, 2018)
Trade in Services can be described as a transaction between a supplier and a consumer without any physical movement of goods across international borders. This, in itself, presents major economic growth possibilities in both regional and multilateral terms. Regional trade agreements, if drafted to suit the specific region's strengths, can promote Trade in Services and establish regional integration. The fact that Trade in Services and regional integration, throughout the Southern African Development Community (SADC) specifically, is moving forward at such a slow pace is due to the lack of political ambition and policy makers failing to emphasise the establishment of trade specific regulatory coherence among member states. Given policy’s impact on Trade in Services, regional trade agreements must be designed to address new and emerging issues that, not only haven't been taken up in previous trade agreements, but which is also region specific and focused enough to build on new standards found in other new trade agreements that will boost regional integration. SADC countries are still in process of establishing a regional services market and, as it currently stands, major development possibilities still exist. This study compares the Trans-Pacific Partnership (TPP) with SADC’s Protocol on Trade in Services (PTIS), with the goal to determine the principles that are necessary to establish a regional market for the integration of Trade in Services. It was found that the PTIS lacks such principles and that integration of services throughout the SADC region is highly unlikely if set forth in its current direction. The finding was that the establishment of regional integration of Trade in Services throughout SADC will have to start with regulatory coherence among its members.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31341
Keywords: Modes of trade; Regional integration; Regulatory coherence; Trade in Services

OHADA and the Making of Transnational Commercial Law in Africa - Bashi Rudahindwa, Jonathan (Law and Development Review, 2018)
The Organisation for Harmonisation of Business Law in Africa (OHADA) was established in October 1993 with the ambitious aim of inciting economic development in its Member States. Through the adoption of Uniform Commercial Laws, the organisation is expected to create an enabling environment for business development, thereby providing for a path to economic growth and subsequent development. In light of this professed aim, both the transnational methodological approach and comparative law theories are used in this paper to critically analyse the various processes conducted under the OHADA banner and to engage in discussions on the highly debated role of law as a vehicle for development in sub-Saharan Africa. This exercise, which proves crucial in order to trace its origin within the global governance and law and development theories, allows us to present OHADA as a transnational legal system, while also highlighting both its strengths and limitations.
Keywords: Law and development; Law reform; Legislative unification; OHADA; Transnational law

A critical analysis of the security of foreign investments in the Southern African Development Community (SADC) region - Ngobeni, Tinyiko Lawrence (University of South Africa, 2018)
Foreign investments in SADC are regulated by Annex 1 of the SADC Protocol on Finance and Investments (SADC FIP), as well as the laws of SADC Member States. At present, SADC faces the challenge that this regime for the regulation of foreign investments is unstable, unsatisfactory and unpredictable. Furthermore, the state of the rule of law in some SADC Member States is unsatisfactory. This negatively affects the security of foreign investments regulated by this regime. The main reasons for this state of affairs are briefly explained below. The regulatory regime for foreign investments in SADC is unstable, due to recent policy reviews and amendments of key regulatory instruments that have taken place. Major developments in this regard have been the suspension of the SADC Tribunal during 2010, the amendment of the SADC Tribunal Protocol during 2014 to bar natural and legal persons from access to the Tribunal, and the amendment of Annex 1 during 2016 to remove investor access to international investor-state arbitration, better known as investor-state dispute settlement (ISDS). The regulation of foreign investments in SADC has been unsatisfactory, among others because some SADC Member States have failed or neglected to harmonise their investment laws with both the 2006 and the 2016 Annex 1. Furthermore, SADC Member States such as Angola, Democratic Republic of Congo (DRC), Malawi, Mauritius, Seychelles, Eswatini, Tanzania, Zambia, and Zimbabwe have multiple Regional Economic Community (REC) memberships. This places these Member States in a position whereby they have conflicting interests and treaty obligations. Finally, the future of the regime for the regulation of foreign investments in SADC is unpredictable, due to regional integration efforts such as the recent formation of the COMESA-EAC-SADC Tripartite Free Zone (T-FTA) and the African Continental Free Trade Area (AfCFTA). The T-FTA is entitled to have its investment protocol, while the AfCFTA investment protocol will be negotiated from 2018 until 2020. These developments entail that the 2016 Annex 1 will soon be replaced by an investment protocol at either the T-FTA or AfCFTA levels, thereby ushering a new regime for the regulation of foreign investments in SADC. The unknown nature of the future regulations create uncertainty and instability among foreign investors and host states alike. This study analyses the regulation of foreign investments in terms of Annex 1 and selected laws of SADC Member States. In the end, it makes the three findings mentioned above. In order to address these findings, the study makes four recommendations. The first is that foreign investments in SADC must be regulated at African Union (AU) level, by means of an AfCFTA investment protocol (which incidentally is now the case). Secondly, investor-state disputes must be referred to the courts of a host state, optional ISDS, the African Court of Justice and Human Rights (ACJ&HR) or other agreed forum. Thirdly, an African Justice Scoreboard (AJS) must be established. The AJS will act as a gateway to determine whether an investor-state dispute shall be referred to the courts of a host state, ISDS, the ACJ&HR or other forums. Fourthly, the office of an African Investment Ombud (AIO) must be created. The AIO shall facilitate the early resolution of investor-state disputes, so as to reduce the number of disputes that may end-up in litigation or arbitration.
Keywords: ACH&PR; AfCFTA; African Continental Free Trade Area; African Court for People and Human Rights; African Court of Justice and Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Justice Scoreboard; African Union; COMESA; Commercial treaties; Customs unions; Dispute resolution; EAC; Expropriation; Foreign economic relations; Foreign investment; Free Trade Agreement; ICSID Arbitration Rules; International commercial arbitration; Investments; Investor-State Dispute Settlement; SADC; SADC Protocol; Southern African Development Community; State Responsibility; UNCITRAL Arbitration Rules

Regional trade integration and co-operation in Southern Africa : the case of the Southern African Development Community (SADC) - Mathebe, Mpubane Mox (University of South Africa, 2017)
Mercantile Law
Keywords: Economic integration; Foreign economic relations; Foreign trade regulation; Free Trade; Monetary unions; SADC; Southern African Development Community

The African Union and the Development of African International Criminal Law - Kahombo, Balingene (Freien Universität Berlin, 2017)
This study is situated in the context of the regionalisation of international criminal law. It deals with the development of African international criminal law under the aegis of the African Union (AU). It aims to examine the factors which inform this development, the concept and the content of regional law so laid down for the African continent. The primary objective has been the exploration of theoretical and practical bases for the establishment of a viable system of African regional criminal justice in order to deal with crimes against peace and security in Africa, which put in danger African regional public order. The thesis also examines the relationship between African international criminal law and the global system of international criminal justice, currently dominated by the International Criminal Court (ICC) and the United Nations Security Council. The systemic analysis of these different issues have enabled to reach three main conclusions. First, the development of African international criminal law is not simply a conjectural consequence of the crisis observed within global international criminal law. It is also and chiefly the result of the policy of self-reliance of the AU and its member states aiming to protect and defend African regional public order through the recourse to regional institutions of criminal accountability. Second, the African Union is consequently promoting a system of African regional criminal justice based on three optional models of justice, namely the delegation of jurisdiction to a member state, the creation of hybrid courts with participation of regional judges and the establishment of a regional criminal court. Together with those crimes against peace and security that are of specific concern to the African continent, these models of justice form the core of the content of African international criminal law. However, the viability of the system towards delivering efficient justice remains problematic. There are numerous challenges to overcome, including ratifying the Malabo Protocol of June 2014 instituting the “Criminal Court of the African Union”, promoting judicial cooperation of African states and finding financial resources to support the Court’s actions. Third, African international criminal law is not a replacement of global international criminal law in the continent. There is rather a coexistence of norms and institutions which commands a certain degree of coordinated relationships to avoid competing actions and so inefficiency of justice. This thesis discusses two main approaches to consistent relationships between African regional criminal law and the global system of international criminal justice, namely the hierarchical model and the cooperative approach. It proposes a third alternative approach, that is, the regionalisation of the ICC in conjunction with the principle of regional territoriality.
Keywords: African Court of Justice and Human and Peoples' Rights; African Union; International Criminal Court; International Criminal Law; Regional Territoriality; Regionalisation; Universal Jurisdiction

East African Community Law: Institutional, Substantive and Comparative EU Aspects - Ugirashebuja, Emmanuel; Ruhangisa, John; Ottervanger, Tom; Cuyvers, Armin (Brill, 2017)
East African Community Law provides a comprehensive and open-access text book on EAC law. Written by leading experts, including the president of the EACJ, national judges, academics and practitioners, it provides the most complete overview to date of this increasingly important field. Uniquely, the book also provides a systematic comparison with EU law. EU companion chapters provide concise overviews of EU law and its development, offering valuable inspiration for the application and further development of EAC law. The book has been written for all practitioners, judges, civil servants, academics and students faced with questions of EAC law. It discusses institutional, substantive and jurisdictional issues, including the nature of EAC law, free movement and competition law as well as the reception of EAC law in Partner States.
Keywords: Comparative law

The liability of trade unions for conduct of their members during industrial action - Mlungisi, Ernest Tenza (University of South Africa, 2016)
South Africa has been experiencing a number of violent strikes by trade unions in recent times. The issue is not only to hold unions liable for damage caused during strikes, but also to reduce the number of violent strikes. This study investigates if victims of such violence can hold trade unions liable for the violent acts committed by their members during industrial action. The Labour Relations Act, 66 of 1995 (LRA) makes provision for the dismissal of employees who commit misconduct during an unprotected strike. It also provides the remedy of an interdict and a claim for just and equitable compensation which can be made against the union, during an unprotected strike. It is further possible to hold the union together with its members liable for damages in terms of the Regulation of Gatherings Act, 205 of 1993 (RGA). The study argues that a strike or conduct in furtherance of a strike that becomes violent could lose protection and the trade union should consequently be held liable, in terms of the LRA and/ or the RGA, for damages caused by its members. This study investigates the position in Canada, Botswana and Australia to determine if there could be any other basis upon which to hold trade union liable for the conduct of its members. The study recommends that the common law doctrine of vicarious liability should be developed by the courts to allow trade unions to be held liable for damages caused by members during violent industrial action. Policy considerations and changing economic conditions and the nature of strikes in the Republic favours the expansion of the doctrine of vicarious liability to trade union member relationship.
https://uir.unisa.ac.za/handle/10500/23172
Keywords: Common law; Industrial relations; Interest arbitration; Labor unions; Liability (Law); Secret ballot requirement; South Africa; Strikes and lockouts; Tort liability of labor unions; Trade union denial; Trade union liability

Integration through comparative private law: Four lessons from Cappelletti - Infantino, Marta (International Journal of Constitutional Law, 2016)
The aim of this article is to explore Cappelletti’s most enduring teachings relevant to those who promote global or regional integration of private laws. The article will review Cappelletti’s insights into the dynamic history of law, the need to respect diversity and take into account society’s imbalances, and the duty of comparative lawyers to engage in “applied” interdisciplinary legal research.

The OHADA Common Court of Justice and Arbitration: Exogenous Forces Contributing to Its Influence - Dickerson, Claire Moore (Law and Contemporary Problems, 2016)

Dealing with trade defence instruments in the context of economic integration in Africa - El Taweel, Khaled (University of Pretoria, 2016)
The launching of the T-FTA in June 2015 presents an opportunity for accelerating regional integration in Africa towards the establishment of a single market through deepening COMESA-EAC-SADC integration. This milestone can contribute positively to African development. Nevertheless, it faces different structural and technical challenges, including the risk of aggressive export strategies and unfair trade practices, which may wipe away a substantial part of the integration gains. This could undermine African integration plans and the largely infant industries in Africa, especially since many African countries lack sufficient technical skills, institutional capacity, and the legal framework to deal efficiently and effectively with unfair trade practices and to respond to situations which may require the application of emergency tools to better adapt to economic challenges. Apart from Egypt, Morocco, Tunisia, South Africa and Zambia national Trade Defence Instruments (TDIs) are not well developed. This could further constrain the ambitious African plans of economic integration. The thesis concludes that, although an effective TDI system is crucial for African integration as it can provide the required protection for African infant industries and unlock the potentials of African economic integration, the current African TDI systems are not effective. This is confirmed by the limited resort to TDIs in the African continent and the general perception that an effective TDI system is not a priority on the integration agenda. The concluded T-FTA TDI legal regime is not supportive for African integration plans in the long run. Africa should envisage how to upgrade its TDI system to make better use of the tools available under the WTO to deal with unfair trade measures, including anti-dumping to face dumped imports, countervailing measures to face subsidized imports, and safeguard measures to temporarily suspend concessions in the face of surge in imports. Africa can improve its national and regional TDIs system by learning from more developed TDI systems incorporated by other economic blocks such as the EU, NAFTA, Mercosur, and ASEAN. This thesis submits that the EU TDIs system is the most suitable to the African integration objectives. This submission is made while recognising the different level of development on both sides. The thesis submits that the long-term objective of the T-FTA is to have a regional investigating authority. It draws several recommendations to enhance African TDI system by working on five main categories: (A) The strategic direction; (B) The institutional framework; (C) Enhancing engagements; (D) Application of TDIs; and (E) The supportive factors.
URI: https://repository.up.ac.za/handle/2263/60043
Keywords: Economic integration; Trade defence instruments; Unfair trade practices

Regional Powers and Leadership in Regional Institutions: Nigeria in ECOWAS and South Africa in SADC - Hulse, Merran (KFG The Transformative Power of Europe, 2016)
Regional powers are not always benevolent leaders when it comes to the building of regional institutions. While powerful states – particularly the “new” rising powers – may have a vested interest in regionalism as a means of projecting influence, regional powers may behave as coercive or benevolent leaders, or alternatively display an absence of leadership altogether. The drivers of varying regional power behavior can be attributed to their competing concerns regarding (economic) power, functional efficiency, international legitimacy, and neopatrimonial networks. This paper explores the varying behavior of Nigeria and South Africa in relation to the institutionalization of free trade areas and regional courts within their respective regions. Nigeria has displayed little leadership in ECOWAS trade integration due to domestic opposition; however, a newly-democratic Nigeria’s search for international legitimacy drove the establishment of the ECOWAS Court of Justice. Likewise, South Africa’s search for legitimacy drove its support for the SADC Tribunal, but the competing demands of different audiences led it to abandon this support. South Africa has also displayed leadership in relation to the SADC Free Trade Area; however, its neighbors perceive it as a self-interested, almost coercive actor. The findings suggest that the motivations for regional powers’ behavior vary across time and policy sectors, and that inconsistent behavior is driven by a change in the priority granted to different drivers.
Accepted: 2018-06-08T11:13:32Z https://refubium.fu-berlin.de/handle/fub188/21860

Democracy and Accountable Governance in the SADC Region - Omede, Jolade; Akindola, Rufus; Ngwube, Arinze (African Journal of Politics and Administrative Studies, 2016)
The call for democracy worldwide is based on the assumption that it allows citizens involvement on how they are governed. Being a representative system of government, democracy is projected to make political leadership responsive and responsible to the entire citizenry of the state. Southern Africa region has the most animated economy in sub –Sahara Africa, and democratic ideals appear more firmly established in the region compared to other regions in Africa. This has made the region, among others in the continent, the preferred choice of many migrants from different parts of the world. It is believed that the region has reached its Eldorado. However, a close observation of the politics of that region tends to suggest there has been the institutionalization of democratic rule without commensurate enthronement of responsible and accountable governance. This study systematically examined the political configurations of the region to concretely determine how the practice of liberal democracy in the sub-region has translated to accountable and responsible governance and its overall impact of the living standard of the citizens of the countries of that region. The paper examined accountable governance in the sense that leaders will be able to mange resource of the state for the well being of the populace. The reverse has been the case for the region. Southern Africa needs a developmental and capable state for socio-economic progress and sustainable democracy. This cannot be achieved without responsible political leadership, which would be responsive to the yearnings of the people. The mode of analysis was based on secondary sources and observation method. The paper adopted secondary and observation techniques as the mode of analysis
Keywords: Accountability; Democracy; Development; Governance; Leadership

Law and Development in West and Central Africa OHADA - Winship, Peter (SMU Dedman School of Law Legal Studies Research Paper, 2015)
This seminar paper considers whether OHADA - an experiment in unifying business law in African countries - has been a success. Following a prologue that explains the origins of the paper, the first part of the paper sets out basic information about the Organisation pour l’Harmonisation du Droit des Affaires en Afrique (“Organization for the Harmonization of Business Law in Africa,” known by the acronym OHADA). This part is followed by a review of law and development literature to assess the value of this literature for an evaluation of the success (or not) of OHADA. A third part then focuses on one specific uniform law, the law of secured transactions. The paper concludes that notwithstanding challenges the OHADA institutions exist and have produced uniform business laws for the formal business sector. Whether OHADA has been the cause of increased investment and trade requires studies that have not been carried out.
Keywords: African law; Secured transactions; commercial law; law and development; law reform; unification of law

Toward an Elaboration of a More Pluralistic Legal Landscape for Developing West African Countries: Organization for the Harmonization of Business Law in Africa (OHADA) and Law and Development - Hiez, David; Menétrey, Séverine (The Law and Development Review, 2015)
In Europe and especially in France, the African business law landscape, as well as the legal discourse, for developing West African countries is almost exclusively dedicated to OHADA, the Organization for the Harmonization of Business Law in Africa, created in 1993. While economic development in the Member States is the obvious underlying reason for the modernization and unification of African business law, the exact nature of such development remains uncertain, as does the manner in which a such result can or will be achieved. OHADA’s Uniform Acts are, with some minor exceptions, a carbon copy of French business law. The only goal is to increase international investment, which, in turn, is expected to generate economic development, but all without taking any notice of equality or social justice issues. That, without a doubt, is the reason why OHADA is constantly criticized as a law that benefits foreign investors, while remaining ineffective, even illusory, for local traders. To go beyond the criticism, the authors have decided to focus on the relationship between law and the informal sector and to draw lines between formal and informal rules in the business sector.
Keywords: Informal rules informal sector; OHADA (Harmonized Business Law in Africa); informal rules; informal sector

Business in West and Central Africa: The Legal Framework - an Introduction to the Laws of the OHADA - Hahn, Anne-Catherine; Darbellay Suso, Aline; Desax, Robert; Herzog, Sabine; Meyer, Manuel; Monnier, Philippe; Schnyder, Marion; Zemp, Rafael (Baker & McKenzie, 2015)

The impact of non-operationalisation of the SADC protocol and international transport agreements on cross border road transport movement in the SADC region - Monyepao, Kaine (Working Together to Deliver - Sakha Sonke, 2015)
The failure by Sothern African Development Community (SADC) countries to fully implement the SADC Protocol on Transport, Communications and Meteorology (the Protocol) and bilateral agreements in regard to road transport negatively impacts the seamless movement of cross border road transport and significantly contributes to the challenges faced by the cross border industry as a whole. The full implementation of the Protocol in regard to road transport, and bilateral agreements would lead to efficient cross border transport regulation and transportation and in turn culminate in reduction of challenges facing the sector. This would lead to reduction of transportation costs, improvement in productivity, and accelerated growth in intra-regional trade, regional economic integration and overall SADC socio-economic development. This paper outlines the extent to which the provisions of the Protocol and bilateral agreements have been implemented by SADC countries and the key challenges emanating from the partial operationalisation of the instruments. The paper is based on findings from engagements with key government and private sector stakeholders in the regional transport environment and various research conducted by the C-BRTA between 2011 and 2014. The partial operationalisation of the instruments has resulted in disjointed regulatory frameworks and inability to: holistically address corridor constraints/ non-tariff barriers, facilitate seamless cross border movements, facilitate liberalisation of access to transport markets in the region, harmonise standards and procedures, and facilitate economic growth and trade between SADC countries. It is possible for the SADC region to realise the aspirations set out in the Protocol and bilateral agreements, and this paper outlines some of the solutions. To begin with, there is need for SADC countries to embrace the need to eradicate the existing self-centric regulatory approach limited to micro-needs and market protectionism. This would need to be underpinned by strong orientation towards the need to achieve macro benefits emanating from a regional perspective in regard to regulating cross border road transport movement. Taking off from this departure point, SADC countries can objectively establish a solid ground towards fully operationalising the Protocol and bilateral agreements. This paper outlines some of the interventions that can be implemented to ensure SADC countries fully operationalise the provisions of the Protocol on transport and bilateral agreements.
Accepted: 2016-11-08T12:11:22Z Artwork Medium: PDF Interview Medium: PDF
Keywords: Southern African Transport Conference; Transportation

Building legal bridges: fostering eastern Africa integration through commercial arbitration - Muigua, David K. (Alternative Dispute Resolution, 2015)
This paper explores the feasibility of commercial arbitration as a means to foster the process of Eastern Africa integration. The author proffers an argument in the context of Eastern Africa integration, that commercial arbitration offers a better platform for dealing with commercial disputes that are bound to arise considering the differing personal or state interests in the ongoing Eastern Africa integration, as compared to national Courts. This discourse is premised on the fact that the five member countries making up the East African Community (EAC) have different legal systems and this presents a major challenge in harmonising the various legal systems. This also affects the possible use of courts in managing the potential transnational commercial disputes due to the potentially different rules of procedure and practice. The paper briefly examines the state of commercial arbitration in the EAC Member States with a view to identifying the existing frameworks and any impediments in their effectiveness. Finally, the author makes a case for utilizing commercial arbitration to build bridges and foster Eastern Africa integration for development.
http://erepository.uonbi.ac.ke/handle/11295/81712
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Establishing continental sovereignty in Africa: risk and opportunity in financial integration - lessons for Africa from a legal perspective - Ngwafor Ndeh, Edwin (University of Glasgow, 2015)
This thesis identifies and defines the new African sovereignty. It establishes a modern sovereignty in Africa hatched from the changing nature of sovereignty in which countries come together at various levels or grades of partial surrender of national sovereignty in order to work closer together for their mutual advantage and benefit. To this end, the narrative zooms in on the central issues within the realms of money matters whereby a new model of monetary sovereignty and monetary solutions is designed in an attempt to ease the recurring tensions and challenges of modern national sovereignty in the continent of Africa. As such, this discussion will offer a historical journey through the constitution of sovereignty, to the birth of the nation state and international public law. It develops the theory of the changing nature of sovereignty within the modern state and opens new lines of inquiry for Africa. In this regard, it draws from juxtaposing and mixing elements of regional and global financial integration as well as retaining national financial sovereignty features to form this new design which I dub continental sovereignty. At its core, the thesis will deal with the legal aspects that stem from the co-mingling of legal systems of nation states and communities at the regional and global levels within the context of financial integration. The argument is that the rule of law remains sacrosanct in monetary management. Effective financial integration is the result of properly structured and managed legal frameworks with robust laws and institutions whether at a national, regional or global level. However, the thesis reveals that in order to avoid undermining the progress of Africa’s financial integration project, any solution for Africa must be immersed within a broader global solution where development issues are addressed and resolved and Africa can form a more central part in all relevant international discussion fora. The work will expound these issues by applying them within a regional and global context, with the state of affairs in Africa forming the nucleus. This application consequently presents the six key themes of the thesis which will be considered therein. They are: a.) regional advantage: which exploits the possibilities of deeper and further financial integration between smaller communal arrangements; b.) regional risk and exposure: the extent to which this deeper form of financial integration can spiral out of control if effected too quickly and too ambitiously; c.) global advantage: which considers the merits of global financial integration and the influence exerted by financial laws on the global financial architecture; d.) global risk and exposure: which considers the challenges of global financial integration especially within the background of the Global Financial Crisis 2007-2008; e.) African challenge: which considers the extent to which this analysis impacts the African economic and financial integration agenda; and f.) development challenge: which examines the extent to which global development issues impact the African solution (continental sovereignty) and the need for any solution for the continent to be roped into a broader global solution within which Africa can form an important part. Even though the thesis requests an optimistic undertone on the progress made so far, it unearths the African problem of multiple national sovereignty and multiple overlapping regional sovereignty constituted as the ‘spaghetti bowl’ dilemma. As such, the unique contribution to knowledge on financial integration in Africa can be echoed in these words: Africa‘s financial integration agenda has had little success in authenticating a systematic and dependable legal framework for monetary management. Efforts made have been incomplete, substandard, and not carefully followed through particularly reflected in the impuissant nature of the judicial enforcement mechanisms. Thus, the thesis argues that, any meaningful answer to the problems dogging the continent is inter alia deeply entrenched within a new form of cooperative monetary sovereignty. In other words, the thesis does not prescribe the creation of new laws; rather it advocates the effective enforcement of existing laws.
Keywords: African Integration Project; Crisis response; Financial crisis; Financial integration; Regional systems; Regulation of financial markets; continental sovereignty

Exploring shared governance as an alternative institutional model for the Southern African development community - Nyathi, Mkhululi (University of Pretoria, 2015)
The Southern African Development Community (SADC) was initially established as a coordination conference in 1980 and was transformed into a treaty organisation in 1992. Challenges of lack of coordination, inefficiency and lack of policy harmonisation led to the amendment of the Treaty in 2001. While the amendment of the Treaty served to address some of the challenges of the organisation, it failed to address the core challenge of the democratic deficit inherent in SADC s governance framework. While the SADC Treaty has as part of its principles and objectives the observance and promotion of democracy and the rule of law, both in its own processes and in its Member States, the design of the SADC institutions does not reflect these normative values. Governance of SADC is characterised by excessive executivism under the overarching powers of the Summit of Heads of State or Government. This democratic deficit is most prominently evidenced by the suspension and eventual disbandment of the SADC Tribunal, the only judicial organ of the organisation. The suspension and disbandment of the Tribunal, in addition to the obvious issue of legality that it raises since it was done in the absence of Treaty amendment, also raises the fundamental question of decision making in SADC in general, as the current treaty framework does not provide for meaningful conversation between and among the key institutions of SADC in matters involving policy formulation and implementation. There is also no institution with a strong oversight role in SADC. There is need for constitutional change in SADC if the organisation is serious in its commitment to achieve its objectives, which it has defined as its Common Agenda. This study proposes a treaty based reform process that is informed by the institutional model of shared governance. One of the several core tenets of this model is that in an organisation, there should be meaningful conversation among the internal stakeholders before a decision is made. For such conversation to be meaningful, there should be the broadest possible exchange of information among the components of an organisation. The proposals made by this study include transforming the Secretariat into an effective institution that formulates SADC laws and policies as well as their implementation frameworks; creation of a SADC parliament that would play a meaningful role on the amendment of the SADC Treaty and in the adoption of the budget; and an independent and accessible judicial body with significant powers of review. Shared governance as conceptualised in this study is not a substitute for, nor does it compete with related concepts like constitutionalism, separation of powers, the rule of law and participatory democracy, but in fact complements them. In addition to these proposals, there is a recommendation for the adoption of a robust access to information regime in which the shared governance institutional model would be anchored. There is also a recommendation for a new regime of law making through community legal instruments that would be directly applicable in Member States as opposed to the largely ineffective protocols.
URI: https://repository.up.ac.za/handle/2263/52280
Keywords: Civil society engagement; SADC; Southern African Development Community

Regional Integration in Africa through the Harmonisation of Laws - Simo, Regis Yann (Regional Integration and Policy Challenges in Sub-Saharan Africa, 2014)
Domestic laws on the African continent have been considered inadequate to attract the investment needed for development and economic growth. A crucial catalyst in attracting investment on the continent is law reform. The formulation of legislation has twofold effects: firstly, it is perceived to mitigate the risks associated with doing business in Africa; secondly, it legally obligates African governments to comply with standards of protection accorded to international investors through the regulation of the business environment. The formulation of legislation is a key determinant of the quality of investment attracted to the continent. This Chapter assesses how the Organization for the Harmonization of African Business Law (OHADA) has contributed to regional integration and economic growth on the continent.
Keywords: Africa; Institutions; Law Reform; OHADA; Regional integration

Law and Development à L'Africaine: Evidence from the OHADA's Harmonization Process - Simo, Regis Yann (African Yearbook of International Law, 2014)
Until recently, doing business in developing countries, and in Sub-Saharan Africa in particular, was associated with high risk. Although each investment decision is associated with some risk, there are always obligations incumbent on host States in that regard. However, when domestic law is too obsolete to match the requirements of an evolving investment and commercial environment which it is supposed to regulate, and when its effects are unpredictable, one of the fundamental conditions for attracting investment goes missing. This eventually underscores the need for a legal reform. The phenomenon of 'globalisation' on the one hand, and the need for (developing) countries to integrate their economies into the global market, on the other hand, considerably accentuated the postulate of development through law.Against this background, some African countries, at the dawn of the 1990s, felt a need to 'modernise' their legal systems for the major part inherited from colonialism. In this vein, they entrusted a supranational organ, the OHADA, to perform that legal reform. This paper is an attempt to test the OHADA against the discourse of law as a development engine. Furthermore, this is an assessment of the extent to which OHADA, as a legal tool, could be useful in serving the purpose of regional integration and economic growth in Africa.
Keywords: Africa; Comparative Law; Law and Development; Law and economics; Law and finance; OHADA

Harmonising Public Procurement in the SADC - Harpe, Stephen de la (Journal of Law, Society and Development, 2014)
The promotion of international trade is seen as one of the important instruments to ensure development in developing nations and regions. The history of the World Trade Organisation (WTO) and the drafting of many regional and similar international trade agreements are evidence of this. The Southern African Development Community (SADC) is no exception.1 It is therefore strange that many states that are members of the WTO and actively encourage the opening up of international borders to free trade do not include public procurement2 in such free trade arrangements. This is particularly evident in developing states. If the WTO Government Procurement Agreement (GPA), which is a plurilateral agreement, is considered it is clear that many states do not wish to open their internal markets to competition in the public procurement sphere. It is therefore not surprising that public procurement has been described as the last rampart of state protectionism (Ky, 2012). Public procurement is an important segment of trade in any country (Arrowsmith & Davies, 1998). It is estimated that public procurement represents between 10% and 15% of the gross domestic product (GDP) of developed countries and up to 25% of GDP in developing states (Wittig, 1999). Unfortunately, governments often expect private industry to open up national markets for international competition but do not lead the way. Except for the limited use of pooled procurement,3 no specific provision is at present made for the harmonisation and integration of public procurement in the SADC. In view of the proximity of the member states, the interdependency of their economies and the benefits that can be derived from opening up their boundaries to regional competition in public procurement, the possibility of harmonisation and deeper integration in this sphere needs to be given more attention. The importance of public procurement in international trade and regional integration is twofold: first, it forms a substantial part of trade with the related economic and developmental implications; secondly, it is used by governments as an instrument to address socio-economic issues. Public procurement spending is also important because of its potential influence on human rights, including aspects such as the alleviation of poverty, the achievement of acceptable labour standards and environmental goals, and similar issues (McCrudden, 1999). In this article the need to harmonise public procurement in the SADC in order to open up public procurement to regional competition, some of the obstacles preventing this, and possible solutions are discussed. Reference is made to international instruments such as the United Nations Commission on International Trade Law (UNCITRAL), the Model Law on Public Procurement and the GPA. In particular, the progress made in the Common Market for Eastern and Southern Africa (COMESA) with regard to the harmonisation of public procurement, which was based on the Model Law, will be used to suggest possible solutions to the problem of harmonising public procurement in the SADC.

Political and Economic Integration in the SADC: Reforming the Energy Sector Regulatory System - Jobodwana, Z. Ntozintle (Journal of Law, Society and Development, 2014)
The Southern Africa Development Community (SADC), the African Union (AU) and other African regional economic communities (RECs) have as their ultimate objective the political and economic integration of the African continent. The SADC is home to a number of countries, all of them striving to improve their investment climate to attract foreign investors by reducing the costs of doing business in the region. One way of achieving this is by setting targets for and speeding up political and economic integration, improving interconnectivity and thereby enlarging the market size and enhancing its attractiveness. The SADC region still suffers from high levels of energy poverty through low access levels in all countries except South Africa and Mauritius. Numerous studies have shown that greater regional trading and cooperation on power development within the SADC could substantially reduce investment and operational costs as well as carbon emissions. The need for a regional power trading pool and regional cooperation grew out of the power utilities’ recognition of the vulnerability of individual countries if each continued to pursue a policy of self-sufficiency rather than out of a desire to minimise the social or financial costs of the region’s power. The power sector in southern Africa is undergoing tremendous reforms, more especially since the establishment of the Southern African Power Pool (SAPP) in August 1995. The SADC, however, faces serious challenges that include diminishing surplus generation capacity and the need to ensure that SADC citizens have equitable access to electricity at affordable prices. To meet these challenges, treaties and protocols have been adopted but are failing to deliver at the implementation stage. This article reviews the SADC energy-electricity regulatory framework in the context of economic and political integration and recommends the establishment of an independent regional regulatory authority to oversee the implementation of integrated holistic energy and air pollution control and prevention, and a common climate change policy. Such a regulator would be a highly resourced regional institution that will liaise with international institutions. This independent regional authority will serve as a catalyst for regional economic integration. It will also have a mandate to introduce and coordinate the establishment of an SADC regional emissions trading scheme that will contribute to managing the mitigation of greenhouse gases (GHGs) and the implementation of global warming adaptation strategies in the region.
Keywords: Climate change; Economic integration; Energy regulation; GHGs; Global warming; Political integration; Regional independent regulatory authority; SADC; SAPP; Treaty regime; UNFCCC

Harmonising the law of sale in the Southern African Development Community (SADC) : an analysis of selected models - Shumba, Tapiwa (Stellenbosch University, 2014)
It is generally recognised that diversity of laws may act as a barrier to the development of trade, both at international and regional level. In a globalised era, trade is necessary for economic development and ultimately for the alleviation of poverty. Although the WTO has done extensive work towards the removal of tariff barriers, there is also a need to focus on addressing non-tariff barriers which include legal barriers to trade. Institutionalised legal harmonisation at an international level has provided the necessary impetus for the development of harmonised laws in the area of international trade. The creation of regional economic communities within the purview of the WTO has also given rise to the necessity of legal harmonisation to facilitate intra-regional trade. A number of regional economic communities and organisations have noted legal harmonisation as one of their areas of regional cooperation. This study focuses on the need to harmonise the law of international sale within the SADC region in order to facilitate cross-border trade. The study points out that the harmonisation of sales laws in SADC is important for the facilitation of both inter-regional and intra-regional trade with the aim of fostering regional integration, economic development and alleviating poverty. Although the necessity of harmonising sales laws has been identified, no effort to this end exists currently in the SADC region. This study addresses the mechanisms by which such harmonisation could be achieved by analysing three models which have been selected for this purpose, namely the CISG, the OHADA and the proposed CESL. The main issues addressed include whether SADC Member States should adopt the CISG, join OHADA, emulate the CESL or should use any of the other instruments as a model for creating a harmonised sales law for SADC. In conclusion, it is observed that SADC has its own institutional and operational mechanisms that require a process and instrument tailor-made for the unique needs of the region. It is recommended that SADC should create its own common sales law based on the CISG but taking into account lessons learnt from both the OHADA system and the CESL. A number of legislative, institutional and operational transformative and reform mechanisms are recommended to enable the creation of such a community law and ensure its uniform application and interpretation.
Keywords: Africa; Economy; Foreign trade promotion; International unification; Mercantile law; Regional disparities; SADC; Southern African Development Community; Trade law

Diaspora, African Union and Sustainable Regional Integration in Africa - Asogwa, Felix; Didiugwu, Ifeanyi (African Journal of Politics and Administrative Studies, 2014)
The role of African Union in the African integration project has remained a topical issue among scholars. Various views have been canvassed on how to strengthen African Union for a more effective regional integration in Africa. This paper examined the central role the African Diasporas can play in repositioning African Union for a sustainable regional integration in Africa. Its analysis of the situation was anchored on the mo-functionalist integration framework and applied essentially the secondary data gathering techniques. Among other recommendations, it suggested for the creation of a pan-African Diaspora Organization.
Keywords: African; Diaspora; Regional integration

Globalization and Private International Law in Commonwealth Africa - Oppong, Richard (University of Arkansas at Little Rock Law Review, 2014)

Nuclear energy in Africa : a legal framework for sustainable energy access - Barnard, Michelle (North-West University, 2014)
The promotion of sustainable development is an objective shared by African Union (AU) member states and the pursuance thereof is expressly mandated by the Constitutive Act of the African Union, 2000 and the Treaty Establishing the African Economic Community, 1992. Lack of access to modern energy sources, such as electricity and the heavy reliance on traditional biomass as primary energy source are factors contributing to the non-achievement of the promotion of sustainable development. These factors are collectively referred to as energy poverty. The African Continent as a whole has limited, and in some instances, lack access to modern energy sources while the majority of its population relies heavily on traditional biomass as primary energy source. Africa can accordingly be classified as an energy poor region–a situation which does not bode well for the promotion of sustainable development. Access to reliable, affordable, economically viable, socially acceptable and environmentally sound energy services and resources is fundamental to socio-economic development. Mitigating the impacts of energy poverty and more specifically lack of access to modern energy sources on the sustainable development of Africa depends upon ensuring increased access to modern energy sources. The above-mentioned instruments furthermore contain provisions which link regional cooperation on the formulation of coordinated regional law and policy on areas/matters of common concern with the achievement of the objective of promoting sustainable development in Africa. One of the areas of common concerns listed is that of energy. Regional cooperation must accordingly be geared towards the effective development of the continent‘s energy and natural resources; promoting the development of new and renewable energy in the framework of the policy of diversification of sources of energy; and establishing an adequate mechanism of concerted action and coordination for the collective solution of the energy development problems within the AU. The formulation of coordinated energy law and policy should take place with reference to the specific sources of energy to be regulated. In this regard, the provisions of the Abuja Treaty and other sub-regional energy access initiatives list various sources of energy as forming part of a diversified AU energy mix – one of which is nuclear energy. In this study recommendations are made as to what should be embodied in a coordinated AU regional nuclear legal framework aimed at regulating increased access to nuclear energy capable of contributing towards the promotion of sustainable development. The recommendations are based on an examination of relevant international, regional and sub-regional legal instruments and other initiatives.
Keywords: African Union; Coordinated legal framework; Energy access; Energy poverty; Nuclear energy; Regional cooperation; Sustainable development

Sanitary and phytosanitary measures in the SADC region : a South African legal perspective - Joubert, Biandri (North-West University, 2014)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health within specified territories from the risks associated with the introduction and spread of pests and diseases through trade. The World Trade Organisation (WTO) developed an agreement on the application of SPS measures. South Africa is a member of both the WTO and the Southern African Development Community (SADC). In SADC, SPS measures are provided for in the SADC Sanitary and Phytosanitary Annexure to the Protocol on Trade of 1996. International Standard Setting Bodies (ISSBs) facilitate the effective application of the main elements of the relevant SPS agreements, especially harmonization and equivalence by establishing scientifically justified standards on which members may base their SPS measures. The relevant ISSB’s in terms of SPS measures are the OIE, IPPC and Codex Alimentarius. SPS measures have the potential to become or be used as non-tariff barriers to trade (NTBs). The SADC Protocol on Trade 1996 stipulates that policies and measures are to be implemented by members to eliminate existing forms of NTBs. Additionally members may not enforce new NTBs affecting or related to intra-SADC trade. The most relevant South African legislation in the context of SPS measures and this study is as follows: Agricultural Pests Act 36 of 1983, the Agricultural Products Act 119 of 1990; the Fertilizers, Farm Feeds, Agricultural Remedies and Stock Remedies Act 36 of 1947, the Liquor Products Act 60 of 1989, Meat Safety Act 40 of 2000, Foodstuffs, Cosmetics and Disinfectants Act 54 of 1972, Medicines and Related Substances Act 101 of 1965 and National Regulator for Compulsory Specifications Act 5 of 2008. The purpose of this study is to establish to what extent the South African legal framework complies with its obligations in terms of the SADC SPS Annexure to the Protocol on Trade.
Keywords: ISSB; NTB; SADC; SPS; Sanitary and phytosanitary measures; South Africa; WTO

Legitimation of the economic community of West African states (ECOWAS): a normative and institutional inquiry - Nwankwo, Chidebe (Brunel University, 2014)
This thesis was submitted for the degree of Doctor of Philosophy and awarded by Brunel University LondonThis study is an attempt at determining the normative legitimacy of the Economic Community of West African States (ECOWAS). At its core, it scrutinizes the current mandate of the organization following the layering of economic integration objectives with human rights protection, sustenance of democracy, and the rule of law. The study discusses the elements of legitimacy across disciplines mainly, international law, international relations and political science. Legitimacy is eventually split along two divides, the normative and descriptive/sociological aspects. The study traces the normative content (shared/common values) underlying integration in Africa, concluding that integration has been born on new ideals such as human rights, democracy and the rule of law. Expectedly, Regional Economic Communities (RECs) as building blocks of the prospective African Economic Community (AEC) under the African Union (AU) regime are mandated to play a vital role in moving the continent forward upon these values. The inquiry is extended to the institutions of ECOWAS to determine their capacity to effectively implement the new mandate of the organization and operate supranationally. In the process, key legal and institutional shortcomings are discussed, particularly in relation to national institutions. It is argued that while human rights protection enhances the normative legitimacy of ECOWAS, it must not be pursued in isolation. Economic integration and protection of citizens’ rights are co-terminus and mutually reinforcing. Hence, community institutions must reflect this link if they are to be effective. The study concludes on the note that, while ECOWAS possesses layers of legitimacy, and have carried out legitimation steps, it cannot be considered a legitimate organization if Member States continue to be non-compliant with community objectives and if key legal questions remain unaddressed. It is submitted that ECOWAS is merely undergoing legitimation, whether it can eventually be considered a legitimate organization is dependent on addressing the identified challenges
Brunel University Research Archive
Keywords: AU; Democracy; ECOWAS; Human Rights; Humanitarian Intervention; Legitimacy; Peace and Security; Regional integration

Some reflections on the prospects for the harmonization of international business laws in Africa : OHADA and beyond - Fombad, Charles Manga (Africa Today, 2013)
The evidence of developments in the harmonization of international business laws shows that Africa is lagging seriously behind. There are still some skeptical voices about the need for and the value of harmonization of international business laws, but such voices are now in a minority. The aim of this paper is to assess the prospects for harmonizing international business laws in Africa. The main contention is that the debate today in Africa is not whether or not there should be harmonization of international business laws, but how this should be done. The paper reviews the imperatives for harmonization and the options that exist and then focuses on the present approach to harmonizing business laws in Africa under the auspices of the Organization for the Harmonization of Business Laws in Africa, better known under its French acronym, OHADA. Based on the critical review of the weaknesses and strengths of the OHADA regulatory framework, the paper suggests ways in which the agenda to develop a harmonized and modern set of business laws in Africa can be achieved.

Common Problems Affecting Supranational Attempts in Africa: An Analytical Overview - Fagbayibo, Babatunde Olaitan (Potchefstroom Electronic Law Journal, 2013)
Ever since the colonial era, attempts have been made throughout the various regions of Africa at building supranational units chiefly for administrative and legal convenience. Examples of such attempts include the Federation of Rhodesia and Nyasaland, the East African High Commission and the federations in former French West and Equatorial Africa, all of which were attempts at forging a supranational nation state. These experiments laid the foundation for further supranational initiatives in post-colonial Africa. In this respect, every region in Africa has either experimented with or is currently experimenting with the idea of supranational regional organisations. This article aims at investigating selected attempts at supranationalism on the continent, the successes and failures of such experiments, and the lessons to be learnt from them. As Africa embarks on the journey of solidifying its unity through the establishment of leviathan continental institutions, efforts should be geared towards building on the experiences of past and present experiments at the sub-regional level. Such experiments offer instructive lessons as they are rooted in similar historical and social contexts.
Keywords: African integration; Central African Economic and Monetary Community; East African Community; Economic Community of West African States; OHADA; Southern Africa Customs Union; Supranationalism; West African Economic and Monetary Union

Legal Innovation for Development: The OHADA Experience - Frilet, Marc (Legal Innovation and Empowerment for Development, 2013)
The World Bank legal review gathers this input from around the world and compiles it into a useful resource for all development practitioners and scholars. The subtitle of this volume, legal innovation and empowerment for development, highlights how the law can respond to the chal-lenges posed to development objectives in a world slowly emerging from an economic crisis. The focus on innovation is a call for new, imaginative strategies and ways of thinking about what the law can do in the development realm. The focus on empowerment is a deliberate attempt to place the law into the hands of the poor; to give them another tool with which to resist poverty. This volume shows some of the ways that the law can make an innovative and empowering difference in development scenarios. Development problems are complex and varied, and the theme of innovation and empowerment naturally has a broad scope. Consequently, this volume reaches far and wide. It considers the nature, promise, and limitations of legal innovation and legal empowerment. It looks at concrete examples in places such as Africa, the Asia-Pacific region, and Latin America. It considers developments in issues with universal application, such as the rights of the disabled and the effectiveness of asset recovery measures. The theme of legal innovation and empowerment for development complements substantive and institutional sensibilities in current development policy. Substantively, development policy discourse seems to have moved away from tacking hard toward statist policy or neoliberal policy. Although this brief introduction cannot do justice to the richness and complexity of these contributions, it does consider each focal point in turn.

The development of a commercial law structure in the SADC with specific reference to OHADA - Leno, Ngaundje Doris (University of Pretoria, 2013)
In a region where there is diversity of laws, the author maintains that law reform is a catalyst for investment and development. This thesis aims at demonstrating that OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC. This is following OHADA’s success in developing uniform commercial rules that are directly applicable in the contracting states. To achieve this, the thesis uses a “structured focused comparison” methodology that allows for two separate, but structurally linked accounts of the structures of both organisations. In exploring the structures of both organisations, the thesis endeavours to: determine whether there is the need for the development of a commercial law structure in the SADC; whether such a structure can be developed within the current SADC structure and whether OHADA can serve as a possible model for the SADC. The findings show that no part of the African continent has witnessed regional legal reform on the scale of that initiated by OHADA. It equally reveals the absence of a uniform commercial law structure in the SADC and the lack of supranational structures to adopt full panoply of business laws and to preserve the uniformity of laws in the member states. The findings from this thesis provide evidence that there is the need forthe development of a commercial law structure in the SADC and improvement of the current SADC structure. There is no doubt that thi swould do away with legal uncertainty in cross-border commercial transactions among SADC states.
Accepted: 2016-05-20T09:04:41Z URI: https://repository.up.ac.za/handle/2263/52731

The Quest for a Supranational Entity in West Africa: Can the Economic Community of West African States attain the Status? - Lokulo-Sodipe, Jadesola O.; Osuntogun, Abiodun J. (Potchefstroom Electronic Law Journal, 2013)
To reflect the growing trends in the international scene and in furtherance of the objective of its Revised 1993 Treaty, the Economic Community of West African States (ECOWAS) summit in December 2006 revolutionised the structure of ECOWAS by re-designating the Executive Secretariat into a quasi-independent commission headed by a President with a Vice President and seven commissioners. The rationale behind the revision was to make ECOWAS a supranational entity. This article considers whether or not a supranational system is essential for the attainment of ECOWAS' objectives. It asks if the conditions for an effective supranational system are in place in the West African sub-region which could provide a solid foundation for its success and why the quest for a supranational system has not yielded any fruitful result in West Africa. It argues that a retreat from the quest for supranationalism and a return to an inter-governmental system would be a retreat rather than the way forward, and expresses the need for the course of action to be sustained courageously till the impact of integration begins to emerge, and the disguised, patriotic impulse of states to protect their national sovereignty gives way to the full manifestation of ECOWAS as a supranational entity.
Number: 3
Keywords: Community Court of Justice; ECOWAS Commission; Intergovermental organisation; Regional integration; Supranational entity

The regional integration of African trade mark laws: challenges and possibilities - Mupangavanhu, Yeukai (University of the Western Cape, 2013)
Keywords: African Union; Differences; Harmonisation; Intellectual property; Regional integration; Similarities; TRIPs; Trade Mark Directive; Trade marks; Unification

Challenges to political and economic intergration in Africa : A socio-Legal perspective - Mwanawina, Ilyayambwa (North-West University, 2013)
This study is concerned with integration efforts on the African continent. This study sets out to investigate the politico-legal and economic impediments to regional and continental integration efforts in Africa. The documents, processes, and organs of the African Union, as the main continental organisation, are the focal point of this study. In order to achieve this, the study primarily adopted a qualitative approach since the literature involved in this work could not be reduced to a quantitative concept. The study ensured that the premises and the conclusions in this work conform to the principles of reliability and validity and in addition the elimination of bias in this was curtailed by validation and triangulation. This was achieved by the fact that the arguments in this work were not only based on qualitative arguments but, where possible, quantitative data was brought in to validate/ triangulate the qualitative arguments. Evidently, the study would have been incomplete if it did not discuss and evaluate the many regional economic communities that have been established to further the objectives of the Treaty establishing the African Economic Community. One of the major premises that this study discovers is that there is a direct and demonstrable relationship between democracy and economic progress; genuine and sustainable development has to be fostered primarily by securing peace and stability on the African continent. Some of the other key findings of the study include that; a) the ultimate goal of the African Union is full political and economic integration leading to the United States of Africa; b) overlapping memberships to a custom unions are highly detrimental to the state since it has to subscribe resources and political will to two or more different arrangements. c) overlapping memberships cause confusion, inertia and most importantly legal uncertainty thereby stifling trade liberalisation efforts; d) many African states still guard their sovereignty closely and that many perceive that yielding their sovereignty to a continental body is tantamount to losing their independence; e) the African Union infrastructure still lacks supra-national and national institutions that are capable of implementing its values; f) the African Union infrastructure does not contain an institutionalised mechanism for the promotion and management of Union affairs at national level; g) the NEPAD initiatives, the APRM process and the functions of the Peace and Security Council play a positive role in African politico-legal and economic development. It has however been shown that these mechanisms are more reactive than preventative and as such intervene too late in the internal affairs of member states; h) armed conflicts cause a reduction in the per-capita Gross Domestic Product growth rate of a nation experiencing a civil war/ conflicts. i) the African Union has regressed from the original timelines of the African Economic Community. The highest regression being Phase 2 which involves the most critical element of strengthening of African regional integration arrangements and the harmonisation of policies concerned. A thirteen (13) year postponement is noted in this regard. j) Africa's poor intra-trade performance is also attributed to the limited progress among African countries in fostering structural transformation. This structural transformation relates to the building of roads, bridges, railway lines and power grids; In order for the African continent to re-position itself in an attempt to harness the benefits of regional integration, some of the recommendations that the study makes are that; a) the African Union grant supra-national status to institutions of the Union for the equitable and speedy attainment of integration; b) the Union and member states should as soon as possible create mechanisms with decision making powers to manage Union affairs at regional and national level; c) the operationalization of the Pan African Parliament should be pursued with the utmost determination to bring the Parliament to full functionality as a Continental legislative body; d) the operationalization of the African Court of Justice and Human Rights be completed as soon as possible in order to allow the body to function as a fully-fledged continental judiciary. This will ensure that the development of integration jurisprudence from an international law perspective is not delayed. The Court will also pursue the enforcement of Human rights norms and practices; e) the Union should further lead the continent in the following sectors with clear and predictable deliverables; i) the establishment and upgrading of regional land, air, and other means of transportation and communication; ii) the creation of a cross-border power and energy generation and distribution network; iii) the establishment, advancement, and diversification of regional financial and commodity markets; iv) the establishment of a regional higher education system by facilitating wider access through specialization in regional integration; The study further acknowledges that these recommendations are not conclusive since the study of regional integration is still at its infancy and many other ideas on how to strengthen African regional integration still await discovery.

Climate change and Africa : the normative framework of the African Union - Pallangyo, Daniel Mirisho (North-West University, 2013)
There is enough evidence on how climate change consequences will adversely affect Africa despite the fact that it is the continent that has least contributed to the problem. The international climate change regime recognises Africa's vulnerability to climate change and provides for special treatment under the United Nations Framework Convention on Climate Change (the UNFCCC). Thus, the international climate change regime presents an opportunity for African countries to adapt and mitigate the consequences of climate change through the UNFCCC mechanism. However, the international climate change legal regime has not been able to adequately assist African countries to address the consequences of climate change under the vulnerability principle. Although the current international climate change regime requires developed countries to reduce their greenhouse gas (GHG) emissions, Africa needs to take steps itself to address the problem, because it is most vulnerable to the consequences of climate change. The African Union (AU) could play a great role in ensuring that the international climate change regime addresses the consequences of climate change in the region. This could be done through fostering strong African common positions during international climate change negotiations. A strong common position could strengthen African bargaining power and might result in more funding, capacity building and technology development and transfer for adaptation and mitigation programmes under the UNFCCC-Kyoto Conference of Parties. However, reaching a strong common position requires the cooperation of the AU member states. In this context, African regional integration is an opportunity for the AU to foster such cooperation among member states. The Treaty Establishing the African Economic Community (the Abuja Treaty), the Constitutive Act of the AU and the Protocol on the Relations between the AU and Regional Economic Communities (RECs) prioritise regional economic integration and call for states' cooperation, but the call has not yet been heeded. To realise deep and viable African integration, there must be a well-structured institutional and legal framework that defines the relationship between the AU, the AEC and the RECs. African regional integration is also seen as an avenue whereby the AU can create its own regional climate-change regime. In this regard, the AU's and RECs' normative framework on climate change is examined in order to assess whether it adequately integrates climate change issues. This study finds that although Africa is most vulnerable to the consequences of climate change, the AU's and RECs' normative framework on climate change is weak and inadequate to address the problem. The Framework should integrate climate change issues in order to achieve sustainable development. The AU should also ensure that member states ratify the relevant treaties and protocols (the Maputo Nature Convention and the Protocol establishing the African Court of Justice and Human Rights) that have not yet been ratified in order that they may become operational. The Maputo Nature Convention puts sustainable development in the forefront of attention as a reaction to the potentially conflicting environmental and developmental challenges facing the continent (such as climate change), but it is not yet in force. This work finds that human rights law can strengthen the AU's role in addressing climate change through its normative framework. The human rights approach to climate change under the African Charter on Human and Peoples' Rights (the Banjul Charter) is a viable avenue because human rights law forms the basis for states' responsibility based on human rights obligations and principles. The extraterritorial application of the Banjul Charter presents an avenue for AU institutions such as the Human Rights Commission and the African Human Rights Court to curb the effects of climate change through a human rights lens. The future of the AU is presented within the context of a set of recommendations that identify strong African regional integration as an avenue through which the AU can foster the cooperation of member states to address the consequences of climate change in the AU's and RECs' normative frameworks. General recommendations are made on the need for the international climate change regime to pay more attention to issues of funding, capacity building and technology development and transfer on the basis of the vulnerability principle and in relation to the principles of equity and common but differentiated responsibilities and respective capabilities. Also, the AU needs to strengthen its legal and institutional structures to ensure deep African integration that is capable of addressing common challenges such as the consequences of climate change.
Keywords: African Charter on Human and Peoples Rights; African Economic Community (AEC); Climate Change; EAC Treaty; ECOWAS Treaty; Human rights; International climate change regime; Normative framework; Regional integration; SADC Treaty; State cooperation; The Constitutive Act of AU

The harmonisation of rules on the recognition and enforcement of foreign judgments in the Southern African Customs Union - Rossouw, Mandi (University of the Western Cape, 2013)
The thesis considers the approaches followed by the European Union with the Brussels Regime, the federal system of the United States of America under the ‘full faith and credit clause’; the inter-state recognition scheme under the Australia and New Zealand Trans- Tasman judicial system; as well as the convention-approach of the Latin American States. It finds that the most suitable approach for the SACU is the negotiation and adoption by all SACU Member States of a multilateral convention on the recognition and enforcement of foreign judgments, comparable to the 1971 Convention of the Hague Conference on Private International Law; the EU Brussels I Regulation and the Latin-American Montevideo Convention, as complemented by the La Paz Convention. It is imperative that a proposed convention should not merely duplicate previous efforts, but should be drafted in the light of the legal, political and socio-economic characteristics of the SACU Member States. The current legislative provisions in force in SACU Member States are compared and analysed, and the comparison and analysis form the basis of a proposal for a future instrument on recognition and enforcement of foreign judgments for the region. A recommended draft text for a proposed Convention on the Recognition and Enforcement of Foreign Judgments for the SACU is included. This draft text could form the basis for future negotiations by SACU Member States
Keywords: Civil and commercial transactions; Cross-border litigation; Foreign judgments; International Trade; Recognition and enforcement; Regional integration; Trade facilitation

The legal implications of harmonising labour laws in the Southern African Development Community (SADC) region - Okharedia, Akhabue Anthony (University of South Africa, 2012)
The purpose of this research is to explore the need for, and the legal implications of, harmonising labour laws in the Southern African Development Community (SADC). Chapter One highlights a number of factors that call for the harmonisation of labour laws in the SADC region and discusses some of the reasons why labour laws are not well developed in the region. The influence of globalisation on labour standards in southern Africa and the influence of regionalism on the harmonisation of labour laws are discussed at length. The inference that could be drawn from this discussion is that for a regionalisation process in southern Africa to be successful, there is an urgent need to harmonise the region’s labour law system. This thesis confirms that Southern Africa has many lessons to learn from the regional harmonisation of labour law in the European Economic Community and the current European Union. The implementation of international labour standards in southern Africa is investigated. The main areas examined include (1) freedom of association, (2) collective bargaining, (3) forced labour and (4) discrimination. The findings of this investigation show that there is no uniformity in the implementation of International Labour Organisation (ILO) standards in the SADC region and, therefore, it is recommended labour law should be harmonised in terms of ILO standards. In respect of the benefits to be derived from the harmonisation process, an empirical investigation was conducted in the SADC region and the following is recommended: the harmonisation of labour law in the SADC region will help with the implementation of ILO standards, protection of workers against the economic power of employers in the workplace and maintaining similar benefits for migrants in the region.
Keywords: Child labor; Collective bargaining; Compulsory labour; Discrimination in employment; Discrimination in the work environment; Droit du travail; Forced labour; Freedom of association; Harmonisation; International Labour Organization; International Labour Standards; Labour law; SADC

Political Economy of the Harmonisation of Business Law in Africa - Ntongho, Rachael (Journal of Politics and Law, 2012)
This paper examines the current dynamics of regulatory reforms in Africa and its implication on the continent. It analyses the highly political struggle for regulatory dominance of business law in Africa and how this interacts with the preferences and power of select international actors. It illustrates that the struggle between Francophone and Anglo-Saxon sections of society for OHADA to reflect their ideological stance is having a negative effect on the harmonisation process.

Regionalism : lessons the SADC may learn from OHADA - Leno, Ngaundje Doris (THRHR, 2012)
Meeste Afrikastate is klein en het nie die vermoë om effektief aan prosesse van die Wêreldhandelsorganisasie deel te neem nie. Hierdie onvermoë, saam met ander faktore, is die hoofrede vir die voortgesette marginalisering van die kontinent in die globale ekonomie en handel. Ten einde effektief aan genoemde prosesse deel te neem en in die voordele van die geglobaliseerde wêreld te deel, moet Afrikastate integreer. Regionalisme of integrasie is nie ’n doel op sigself nie maar is nodig vir die ekonomiese groei van Afrikastate. Dit skep groter markte vir handel en belegging en is ’n aansporing tot groter effektiwiteit, produktiwiteit en mededingendheid. In die lig hiervan stel die artikel drie kernargumente. Die eerste is dat regionalisme voordele bied wat Afrikastate kan ontgin ten einde marginalisering op globale vlak te oorkom. Die tweede argument is dat, terwyl die Suider-Afrikaanse Ontwikkelingsgemeenskap (SAOG) poog om besigheidsreg te harmoniseer, die Organisation for the Harmonisation of Business Law in Africa (OHADA) (Organisation pour l’Harmonisation en Afrique du Droit des Affaires) as voorbeeld kan dien aangesien dit reeds die grondslag gelê het vir die harmonisering van besigheidsreg in Afrika. Die derde argument is dat die SAOG-tribunaal verbeter moet word ten einde ’n meer regionale regsraamwerk binne die SAOG daar te stel. In hierdie verband belig die artikel sommige voordele van regionalisme in Afrika, die lesse wat die SAOG by OHADA kan leer, die voordele van ’n geharmoniseerde besigheidsreg teen die agtergrond van die OHADA-ondervinding en die moontlike wyses waarop die SAOGtribunaal verbeter kan word.

Can OHADA Increase Legal Certainty in Africa? - Beauchard, Renaud; Kodo, Mahutodji Jimmy Vital (The World Bank, 2011)
This paper describes the origins, structure, and practical impact of the Organization for the Harmonization of Business Law in Africa (OHADA). It analyzes the institutional framework created via the OHADA Treaty and the legal, jurisprudential, and functional challenges that OHADA Member States are still grappling with. Details of the nine substantive laws that have so far been ratified as uniform acts by means of the treaty have also been provided. The authors conclude that in making OHADA law effective, Member States face continuing and substantial resource deficits, institutional deficiencies, language ambiguities, and intransigent official attitudes toward the need for appropriate mechanisms for the pursuance and enforcement of OHADA laws and processes.

Multi-Membership and the Effectiveness of Regional Trade Agreements in Western and Southern Africa: A Comparative Study of ECOWAS and SADC - Afesorgbor, Sylvanus Kwaku; Van Bergeijk, Peter A. G. (Proceedings of the German Development Economics Conference, 2011)
Using a gravity model for 35 countries and the years 1995-2006 we estimate the impact of regional trade agreements in Africa (in particular ECOWAS and SADC) and compare this to the a benchmark of North South trade integration (Europe‟s preferential trade agreement). We find that  ECOWAS and SADC membership significantly increases bilateral trade flows (and by more than for example preferential trade agreements with the EU do),  SADC membership has a stronger impact compared to ECOWAS and  that the impact of multi-membership critically depends on the characteristics of the overlapping RTA We find a positive impact if an additional membership complements the integration process of the original RTA: overlapping memberships had a significant positive effect on bilateral trade within the ECOWAS bloc but it is insignificant for SADC.

Comparative regionalism: a new research agenda - Börzel, Tanja A. (KFG The Transformative Power of Europe, 2011)
After the end of the Cold War, students of International Relations observed an expansion of inter-state activities at the regional level. Regional and sub-regional groupings appeared to gain momentum as the way in which countries cooperate and should cooperate to pursue peace, stability, wealth and social justice. The surge and resurgence of regionalism has triggered the proliferation of concepts and approaches. The focus of this paper will be on processes and structures of state-led regionalism driven by the delegation of policies and political authority to regional institutions. Based on this understanding of regionalism, the existing literature will be reviewed with regard to three general questions. These questions do not only require research across regions but also allow developing a common research agenda to accumulate knowledge generated about specific regions. First, what are the outcomes of regionalism? How can we describe and compare the results of the delegation of policies and political authority? Second, what are the drivers of regionalism? Why do some governments choose to delegate policies and political authority while others do not? Finally, what are the internal effects of regionalism? How does the delegation of policies and political authority impact back on the domestic structures of the states involved?
Accepted: 2018-06-08T07:36:10Z

Challenges to regional intergration in the SADC region : a legal perspective - Mwanawina, Ilyayambwa (North-West University, 2011)
The Southern African Development Community (SADC), formerly known as the Southern African Development Coordination Conference (SADCC), is an organization of Southern African states initially formed to reduce economic dependence on South Africa (then an Apartheid state) and to harmonize and coordinate development in the region. The vision and mission of SADC reach well beyond the harmonization of development within the region. It extends to fields that include political stability, peace building, the maintenance of security and justice as well as economic cooperation. The attainment of these goals requires well co-ordinated regional mechanisms; as such over the past decade member states have paid particular attention to the possibility of attaining these goals through regional integration. The transformation from SADCC to SADC indicated that the body would no longer be a loose association (conference) of states but rather a regional body that would have a legally binding effect on its member states. The question is, when the member states assembled in Windhoek, August 1992, did they create an institutional framework, and policies that would have enough legal force to ensure that the institutional agenda of integration is not defeated by member states? The argument of this dissertation is that the Treaty and the policies established afterwards contain principle imperfections that are self defeating for the pursuance of regional integration. The work will begin by discussing regional integration in general, highlighting the historical origins of SADC as well as the role of the African Union. The work will then discuss the dimensions and functioning of SADC, laying the foundation for a proper critique on how the institutional framework contains inherent weaknesses that eventually hinder the progression of SADC. The dissertation ultimately will discuss and benchmark the European Union against SADC, in an attempt to extract important lessons for the progression of SADC.
Accepted: 2016-01-10T22:52:56Z https://repository.nwu.ac.za/handle/10394/15788
Keywords: Africa; Interregionalism; Southern

A politico-legal framework for integration in Africa : exploring the attainability of a supranational African Union - Fagbayibo, Babatunde Olaitan (University of Pretoria, 2010)
The emergence of the African Union (AU) is seen as an effort to reposition Africa for the challenges of contemporary global realpolitik and, in particular, it provides a road map towards the attainment of a political union. The institutional architecture of the AU, modelled after the European Union (EU), indicates an intention on the part of the architects of the AU to endow the organisation with supranational attributes. However, none of its institutions has as yet started to exercise supranational powers. It is against this background that this thesis explores the feasibility of transforming the AU from a mere intergovernmental organisation into a supranational entity. In the course of the investigation, it was found that a major obstacle to realising this is the absence of shared democratic norms and standards, a consequence of the unconditional membership ideology of the AU. This thesis argues that the starting point of closer integration in Africa should be the cultivation and adoption of shared norms and values. To address this, the study proposes that the AU design an institutional mechanism for regulating its membership. Using the African Peer Review Mechanism (APRM) as a case study, this study shows that it is possible to establish a regulatory regime based on strict adherence to shared fundamental norms and values. A major recommendation is the transformation of the APRM into a legally binding instrument for setting continental democratic standards, assessing whether member states fulfil these standards and ultimately determining which member states are qualified, based on objective standards, to be part of a democratic AU.
https://repository.up.ac.za/handle/2263/28573
Keywords: African Union; African peer review mechanism; Regional economic communities (RECs); Regional integration

The New African Law: Beyond the Difference Between Common Law and Civil Law - Mancuso, Salvatore (Annual Survey of International & Comparative Law, 2010)

The Role of South Africa in SADC Regional Integration: the Making or Braking of the Organization - Amos, Saurombe (Journal of International Commercial Law and Technology, 2010)
Read on Neliti

Future Directions of Legal Harmonisation and Law Reform : Stormy Seas or Prosperous Voyage ? - Faria, José Angelo Estrella (Uniform Law Review, 2009)

The need to harmonise trade-related laws within countries of the African Union: an introduction to the problems posed by legal divergence - Dlagnekova, Polina (Fundamina : A Journal of Legal History, 2009)
It is widely accepted that inter-state relationships have entered an era of globalisation. The economic theory of convergence explains that it is this phenomenon which has spearheaded, amongst others, the development of international rules in the field of trade, finance and taxation.

Unified Business Laws for Africa: Common Law Perspectives on OHADA - Dickerson, Claire Moore (GMB Publishing Ltd, 2009)

The Role of International Economic Law in Africa - Obale, Offah Ako (Social Science Research Network, 2008)
International Economic law (IEL) has a specific role to play in a complex modern Africa. The underdeveloped state of trade law regimes in Africa is arguably a reflection and product of the low level of commercial activity. The reverse is equally true in that underdevelopment in commercial activity on the continent is a reflection and product of the minimal role played thus far by international economic law.
Keywords: AEC; Africa; African; African Economic Community (AEC); Doha; Globilisation; International Economic Law; OHADA; Trade law; WTO

Reforming Legal Reform in Francophone Africa: World Bank' Project Experience - Wabnitz, Hans-Werner (Islamic Law and Law of the Muslim World Paper, 2008)
You don't plant water lilies in the desert - The keystone of civilized society is justice. Without justice, neither peace nor development. A prerequisite is the populations' trust in legal institutions: the law and the courts. The alienation of the people with imposed legal institutions is the reason for Francophone Africa's lack of justice. To remedy the situation, this paper proposes to reconnect the people with the law through: (1) respecting local values in Village tribunals; (2) reforming lawmaking to comply with custom, accessible (also) in vernacular languages; (3) accessibility of law through the Internet. It is argued that the people, as client of justice, need to regain control over their law in order to respect it. Only then the necessary change of traditions and values is feasible. Women lawyer associations are identified as agents for such change. To redress modern courts, the paper suggests a concentration of tribunals, a tightening of procedure and rigorous control, in order to foster peer pressure for professionalism. The constitutional values are to serve as common bond.
Keywords: ACCESS TO JUSTICE; Africa; Colonial law; Corruption; Court administration; Culture; Customary law; Drafting; Equality; Fatwa; Gender; Honor; Human rights; Institutions; Justice; Law; Legal reform; OHADA; Paralegals; Participation; Reform; Tradition; Uniform Act; Village courts; Worldbank

Some preliminary thoughts on a comparative law model for harmonisation of laws in Africa - Nicholson, Caroline (Fundamina : A Journal of Legal History, 2008)
This paper is premised upon acceptance of the view that some form of harmonisation of laws in Africa is a desirable objective and that comparative legal research is a tool that might effectively be applied in order to further the objective of harmonisation. That said, the time has come for comparatists in Africa to think afresh on the issues of globalisation and the need for harmonisation of laws in Africa, with a view to promoting peace, stability and scope for increased development in the region through greater regional economic co-operation.

NEPAD and African Development: Towards a New Partnership between Development Actors in Africa - Tawfik, Rawia M. (African Journal of International Affairs, 2008)
The model required to drive socio-economic development in Africa, and the relationship between the state and the private sector based on that model, have sparked much controversy among African analysts. Some question the relevance of other successful models of development, such as in the liberal West or in East-Asia, to the African context. Others criticise all models of development that are “alien” to African cultures and conditions hence rejecting the NEPAD model on this basis. This paper argues that although NEPAD does not present a detailed model of the relationship between the state, the private sector and civil society in Africa, some of its theoretical underpinnings suggest a balanced framework that should prompt African scholars to search for new models that do not necessarily imitate already successful ones but respect the particularities of each African state

The Harmonization of Business Law in Africa: Is Article 42 of the OHADA Treaty a Problem? - Enonchong, Nelson (Journal of African Law, 2007)
OpenAlex: https://openalex.org/W2023472476
Keywords: Harmonization; Investment; Member state

Re-Imagining International Law: An Examination of Recent Trends in the Reception of International Law Into National Legal Systems in Africa - Oppong, Richard (Fordham International Law Journal, 2006)
This article suggests that the trend of accepting the supremacy and direct application of international law represents a rethinking of the relationship between international and national law, and that its full implications are yet to be explored. The Article seeks to build on current writings on the subject by analyzing certain regional arrangements and judicial approaches relevant to, but often ignored in the discussion. It attempts not to situate these arrangements or approaches within or outside of the monist/dualist paradigm, but to assess the practical significance of these arrangements for international law, national law, and their respective subjects.

The Social Dimension of Regional Integration in ECOWAS - Robert, René (Social Science Research Network, 2004)
Regional economic integration arrangements have their own purpose, legal framework, institutional set-up, history, and trajectory, and this paper aims to study these factors in relation to the Economic Community of West African States (ECOWAS). When dealing with regional integration, it is important to consider governance, trade liberalization, and its social impact. The paper focuses on the West African Economic and Monetary Union (WAEMU) and the Organization for the Harmonization of Business Law in Africa (OHADA) to analyze labour law harmonization, poverty reduction strategies for development, gender empowerment, and democratic participation. Suggestions to strengthen socio-economic development include promoting social dialogue and how the International Labour Organization and other institutions' can help with better integration in Western Africa. Ultimately, identifying and understanding the unique economic integration arrangements of certain communities can help develop their paths towards a fairer globalization for all.
10.2139/ssrn.908485
Keywords: ECOWAS; Integration; Regional; Social dimension; WAEMU

Worldwide Harmonisation of Private Law and Regional Economic Integration - General Report - Basedow, Jürgen (Uniform Law Review, 2003)

Business Law in Africa: OHADA and the Harmonization Process - Martor, Boris; Pilkington, Nanette; Sellers, David S.; Thouvenot, Sébastien (GMB Publishing, 2002)
Accepted: 2019-04-10T07:48:19Z Journal Abbreviation: OHADA and the Harmonization Process

African Legal Developments in the United States and Sub-Saharan Africa - Eisenfeld, Jamie; Serres, Francois (The International Lawyer, 2001)
https://scholar.smu.edu/til/vol35/iss3/3

The regional integration of commercial air transport in Africa : political, economic and legal considerations - Kaunda, Gideon H. (McGill University, 1983)
The introduction of this dissertation discusses geopolitical and socio-economic factors which influence transportation in Africa. Chapters II and III, respectively, analyse the concept of regionalism and the legal framework of multinational civil aviation co-operation. The economic advantages of surface and air transportation are compared in Chapter IV. Chapter V is a general survey of the impact of nationalism on socio-economic co-operation. To illustrate the extent of political problems, in economic and aeronautical co-operation, the former East African Community is reviewed in Chapter VI. The demised East African regional carrier is specifically discussed in Chapter VII. Chapter VIII highlights the notion in functionalism as an approach to the attainment of socio-economic integration. Multilateral organizations responsible for co-ordinating and fostering co-operation are examined in Chapters IX, X and XI. Current regional activities and future prospects are essessed in the penultimate chapter. The conclusion contains the essential elements required in creating regional airlines in Africa.
Identifier: https://escholarship.mcgill.ca/concern/theses/vd66w0581
Keywords: Africa; Air transport; Commercial air transport; Regional integration

The 1975 Treaty of the Economic Community of West African States - ECOWAS Commission (1975)
Le traité de la Communauté économique des États de l’Afrique de l’Ouest (CEDEAO) est un accord multilatéral signé par les États membres qui formaient la Communauté économique des États de l’Afrique de l’Ouest. Le traité initial a été signé par les chefs d’État et de gouvernement des 16 États membres de l’époque en 1975 à Lagos, au Nigeria. Avec les nouveaux développements et mandats de la Communauté, un traité révisé a été signé à Cotonou, en République du Bénin, en juillet 1993 par les chefs d’État et de gouvernement des États membres actuels.